Effectiveness of Film Media in Improving Students' Knowledge and Attitudes Towards Clean and Healthy Living Behavior (PHBS) at Darul Fikri Islamic Boarding School Sungai Belidak - Muhammad Aji Abdurrahman; Selviana; Elly Trisnawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Clean and Healthy Living Behavior (PHBS) is a set of behaviors practiced based on awareness of learning outcomes. Public health can be improved by changing behavior from unhealthy to healthier. Health education is needed to increase awareness, willingness, and ability to live healthily. Health education methods are generally carried out through lectures and presentation media. The use of visual and audiovisual media can attract the attention and focus of targets, thereby increasing effectiveness. Objective: This study aims to improve the knowledge and attitudes of students about PHBS in the Darul Fikri Sungai Belidak Islamic Boarding School environment. Method: This study used a quasi-experimental design with a one group pretest-posttest design approach. It was conducted at the Darul Fikri Islamic Boarding School, Sungai Belidak from July to October 2024, with a population of all students. The sample consisted of 30 respondents taken using a purposive sampling technique. Data analysis was carried out using univariate and bivariate analysis using the paired sample t-test. Results: The average value of pre-test knowledge was 8.93, while the post-test increased to 12.23 (difference 3.3). The average value of pre-test attitude was 44.60, while the post-test increased to 48.77 (difference 4.17). Before education, 40% of students had good knowledge, increasing to 76.7% after education. The good attitude of students increased from 46.7% to 73.3%. The paired sample t-test showed a sig value of 0.000 (p <0.05) for knowledge and 0.019 (p <0.05) for attitude, which indicated a significant influence of PHBS education using film media. Conclusion: It can be concluded that there is a positive influence between attitudes and knowledge towards PHBS education in Islamic boarding schools using film media. PHBS counseling through film media is very effective in improving the knowledge and attitudes of students, so that students are expected to be able to learn and understand knowledge well.